The fate of wetlands: can the view from space help us to stop and reverse their global decline? - Strauch, A.; Bunting, P.; Campbell, J.; Cornish, N.; Eberle, J.; Fatoyinbo, T.; Franke, J.; Hentze, K.; Lagomasino, D.; Lucas, R.; Paganini, M.; Rebelo, Lisa-Maria; et al. (Wiley, 2022)
Wetlands are among the most vulnerable, threatened, valuable, diverse, and heterogeneous ecosystems existing on our planet. While they provide invaluable ecosystem services to our society, they have been declining globally for many centuries. Monitoring of these changes is necessary for implementing efficient conservation policies and sustainable management schemes. Earth observation techniques can support the effort of monitoring, assessing, and inventorying wetlands at different scales with ever growing capabilities and toolsets. While the GEO-Wetlands initiative provides a framework for collaboratively increasing and utilizing these capabilities, global stakeholders like the Ramsar Convention on Wetlands and U.N. Environment are starting to adopt EO-based methods in their guidelines and technical reports. Many challenges still remain, although different projects and case studies successfully demonstrate the opportunities provided by the growing data archives, analysis algorithms, and processing capabilities. Many of these demonstrations focus on local wetland sites. The mapping and inventorying, specifically of vegetated wetlands, on national or even global scales remains a challenge for the wetlands and EO communities for years to come. Collaboration and partnership between different stakeholders of both communities are key for success. Initiatives like GEO-Wetlands, in cooperation with global stakeholders, need to provide the framework for this collaborative effort.